2015
DOI: 10.15252/embr.201439496
|View full text |Cite
|
Sign up to set email alerts
|

RIP 1 negatively regulates basal autophagic flux through TFEB to control sensitivity to apoptosis

Abstract: In a synthetic lethality/viability screen, we identified the serine-threonine kinase RIP1 (RIPK1) as a gene whose knockdown is highly selected against during growth in normal media, in which autophagy is not critical, but selected for in conditions that increase reliance on basal autophagy. RIP1 represses basal autophagy in part due to its ability to regulate the TFEB transcription factor, which controls the expression of autophagy-related and lysosomal genes. RIP1 activates ERK, which negatively regulates TFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Recently, it has been shown that RIP1 negatively regulates basal levels of autophagy in a kinase-independent manner (Yonekawa et al, 2015). The negative regulation of autophagy by RIP1 was accomplished through the phosphorylation and consequent negative regulation of TFEB, a transcription factor that induces expression of autophagy-related genes (Yonekawa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that RIP1 negatively regulates basal levels of autophagy in a kinase-independent manner (Yonekawa et al, 2015). The negative regulation of autophagy by RIP1 was accomplished through the phosphorylation and consequent negative regulation of TFEB, a transcription factor that induces expression of autophagy-related genes (Yonekawa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The negative regulation of autophagy by RIP1 was accomplished through the phosphorylation and consequent negative regulation of TFEB, a transcription factor that induces expression of autophagy-related genes (Yonekawa et al, 2015). Whereas RIP1 is required for TNFα-induced RIP3-dependent necroptosis, recent evidence has shown that RIP1 negatively regulates TRIF-mediated, IFN-mediated and spontaneous RIP3-dependent necroptosis in a kinase independent fashion (Dillon et al, 2014; Kaiser et al, 2014; Rickard et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although autophagy can protect against cell death, apoptosis can suppress autophagy, inducing caspase-mediated cleavage of essential autophagy proteins such as Beclin 1 56 . Moreover, RIP1 also represses basal autophagy by activating ERK and subsequently inhibits TFEB-mediated expression of autophagy-related and lysosome genes 57 .…”
Section: Interactions Of Apoptosis Necrosis and Autophagymentioning
confidence: 99%
“…In addition, RIP1 also activates ERK and represses basal autophagy by inhibiting TFEB-mediated expression of autophagy-related and lysosomal genes (Yonekawa et al, 2015). Therefore, there is a complicated mutual regulatory network among autophagy, apoptosis and necroptosis.…”
Section: Other Forms Of Regulated Programmed Cell Death In Aldmentioning
confidence: 99%